PERENCANAAN PEMBANGKIT LISTRIK TENAGA MINI HIDRO DI SUNGAI LOGAWA, KABUPATEN BANYUMAS - Apriadi Ali Ramadhan; Arie Al Asyari; Suharyanto Suharyanto; Abdul Kadir (Jurnal Karya Teknik Sipil, 2013)
Electricity is a basic human need. Human activity will be disrupted if the availability of electrical energy is also affected. This condition is also currently being experienced by the people of Indonesia. There has been an energy crisis in some regions of Indonesia, particularly in Java - Bali where the area is the center of activity in Indonesia. This is indicated by the frequent occurrence of blackouts in rotation as in most cities in Indonesia. The crisis caused by an imbalance between  supply and demand of electricity usage. Meanwhile, the ability of the government, in this case the PLN in providing the electricity needs is very limited. Therefore, the government is encouraging private sectors and communities to participate in the production of alternative energy, one of which is the Mini Hydro Power Plant. Banyumas Regency has a potential river to build as Mini Hydro Power Plant. This mini hydro power plant will utilize the waterflow from the rivers. The electrical energy produced will be supplied to the Java – Bali interconnection network so that electricity supply can increase the Java – Bali capacity. In this  PLTMH  Logawa is planned to generate 616 kWh of power which can serve approximately 600 homes with the assumption that the usage of the power is about  900 watts per hours. It requires investment funds for the construction works amounting to Rp.25,265,787,700,-